Correction to: Integrated Multi-stakeholder Systems Thinking Strategy: Decision-making with Biopharmaceutics Risk Assessment Roadmap (BioRAM) to Optimize Clinical Performance of Drug Products - Selen, Arzu; Müllertz, Anette; Kesisoglou, Filippos; Ho, Rodney J. Y.; Cook, Jack A.; Dickinson, Paul A.; Flanagan, Talia (The AAPS journal, 2020)
A Correction to this paper has been published: https://doi.org/10.1208/s12248-020-00534-0